Do you get where I'm coming from Perceived understanding buffers against the negative impact of conflict on relationship satisfaction. [article]. - Gordon, Amie M.
Conflict can have damaging effects on relationship health. But is all conflict detrimental? Across 7 studies, we tested the overarching hypothesis that conflict in close relationships is only detrimental when people do not feel their thoughts, feelings, and point of view are understood by their relationships partners. Supporting this, conflict was negatively associated with relationship satisfaction among participants who perceived their romantic partner as less understanding, but not among those who felt more understood by their partners. This was true cross-sectionally (Study 1), experimentally (Studies 2, 3, 6a, and 6b), in daily life (Study 4), and for both members of couples pre-to postconflict conversation in the laboratory (Study 5). The buffering effects of feeling understood could not be explained by people who felt more understood being more understanding themselves, having more general positive perceptions of their partners, fighting about less important or different types of issues, engaging in more pleasant conflict conversations, or being more satisfied with their relationships before the conflict. Perceived understanding was positively associated with conflict resolution, but this did not explain the benefits of feeling understood. Evidence from Studies 6a and 6b suggests that feelings understood during conflict may buffer against reduced relationships satisfaction in part because it strengthens the relationship and signals that one's partner is invested. overall, these studies suggest that perceived understanding may be a critical buffer against the potentially detrimental effects of relationship conflict. -- (from the authors)